1985
DOI: 10.1073/pnas.82.20.6797
|View full text |Cite
|
Sign up to set email alerts
|

Immunization of rabbits with purified RNA polymerase I induces a distinct population of antibodies against nucleic acids as well as anti-RNA polymerase I antibodies, both characteristic of systemic lupus erythematosus.

Abstract: Rabbits were immunized with either RNA polymerase I or poly(A) polymerase that had been purified to apparent homogeneity and was devoid of nucleic acids. Sera from rabbits thus immunized were screened for antibodies against nucleic acids. All seven rabbits injected with RNA polymerase I but none of the four rabbits immunized with poly(A) polymerase produced anti-nucleic acid antibodies. Anti-RNA polymerase I antibodies were induced after a single injection of the enzyme. Anti-polynucleotide antibodies were not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Anti-RNAPI(S1)-NT and -BD antibody production by rabbits immunized with lupus anti-DNA We reported previously that rabbits immunized with purified rat hepatoma RNAPI holoenzyme produce anti-DNA antibodies [34]. Subsequently, we reported that affinity purified anti-DNA (IgG or IgG Fab) from SLE patients or lupus mice produced anti-RNAPI antibodies directed primarily against the S1 of the polymerase [35,36].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Anti-RNAPI(S1)-NT and -BD antibody production by rabbits immunized with lupus anti-DNA We reported previously that rabbits immunized with purified rat hepatoma RNAPI holoenzyme produce anti-DNA antibodies [34]. Subsequently, we reported that affinity purified anti-DNA (IgG or IgG Fab) from SLE patients or lupus mice produced anti-RNAPI antibodies directed primarily against the S1 of the polymerase [35,36].…”
Section: Resultsmentioning
confidence: 98%
“…Previously, we reported that immunization of rabbits with RNA polymerase I (RNAPI) holoenzyme resulted in anti-DNA antibody production [34]. Conversely, immunization of rabbits with anti-dsDNA purified from the sera of SLE patients or lupus mice induced production of anti-RNAPI antibodies directed primarily against the largest subunit (194 kDa; S1) of RNAPI [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…In previous reports it has been shown that the autoantibodies against rat hepatoma RNA pol I were highly specific and did not cross-react with poly(A) polymerase (25). Therefore, we have examined whether the TSK mAbs also exhibit a similar property by competitive inhibition assays.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of anti-RNA pol I antibodies in the sera of patients with systemic sclerosis (7) or other rheumatic diseases (6) and in MRL mice (8) was studied using rat hepatocyte RNA pol I (25). In this study, besides the rat enzyme, we have used bacterial (E. coli) and viral (T7 phage) enzymes, since it is well known that self-epitopes on housekeeping enzymes (15), structural proteins (26), and cell receptors (27) Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In some cases, it was found that the sera raised in this way were able to cross-react with antigens other than the ones used for im munization. For instance, in New Zealand rabbits immu nized with RNA-polymerase, antibodies reacting with nu cleic acids were obtained [7], while in animals of the same breed immunized with a mixture of total histones complexed with RNA, antibodies were produced that reacted with dsDNA, Ub, a peptide of ubiquitinated H2A, pep tides of Sm-D antigen and poly-(ADP)-ribose [8],…”
Section: Introductionmentioning
confidence: 99%